Lógica interna e os princípios didáticos do futsal - Dias, Otávio Figueiró (2022)
Motor Praxeology is a theory whose premise is to study the essence of games and sports, more precisely with regard to the study of the Internal Logic of motor practices. Futsal is a modality with cooperation and opposition interactions, the objective is during the game, to reach the opponent's goal and consequently score a goal, always seeking to facilitate collective actions with his teammates and harm them to his opponent. The internal logic of the game has as its starting point knowing the main rules of the modality and understanding how the characters involved in the game relate to materials, other players, space and time. The teaching methodology based on Conditioned Games for Futsal is aimed at developing specific situations in the sport of Futsal. Creating alternatives in which the purpose is to repeat the actions created in the matches several times. In this way, the participant assumes a leading role in game situations, as he becomes an integral part of the process as a whole. In this perspective, the present study aimed to: Present the Internal Logic (IL) of Futsal and establish the relations of the Futsal LI with the Teaching method of Conditioned Games in view of the Teaching-Learning process of the Futsal modality. Therefore, in article 1 the Internal Logic of Futsal will be presented from a praxeological analysis, in article 2 it will be presented based on Internal Logic, the didactic principles for the teaching-learning process of Futsal having as reference the method of games conditioned and in article 3, the objective is to establish from Motor Praxeology, reflections and approaches for a Scientific Language of the game. It was concluded in article 1 that Motor Praxiology presents important tools for understanding, from scientific knowledge, the Internal Logic of Futsal. In article 2, it is concluded that the work with the teaching and training of Futsal from the perspective of Conditioned Games and Internal Logic constitutes a relevant tool for teachers, coaches and students to understand the world of futsal, including bringing new directions for the construction of a didactic teaching of the game based on the game itself. In article 3, it was concluded that the use of a scientific language that relates theoretical knowledge with the latent practice of teaching and learning in collective games is a necessity so that in the future we can build scientifically guided dialogues and, through this, overcome the jargon that involves the sports scene.